KONFLIK POLITIK SOEKARNO DAN BUYA HAMKA PADA TAHUN 1962-1970 - Septiani, Viska; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Soekarno-Buya Hamka are two great figures whose services to the nation of Indonesia can not be forgotten because they have incised their black and white color for the history of RI (wkwkw ini kalimat perumpamaannya ya? Gatau aku bagusnya buat apa). As an ordinary human being, Soekarno-Buya Hamka are not a perfect. Therefore, these two friendly figures also have flaws despite of their superiority. Both Soekarno and Buya Hamka have the principle of fighting for the Indonesian nation by taking the independence of Indonesia from the hands of invaders. Though they have different thoughts in politic, they still keep in touch. The purpose of this research is to know the beginning of Soekarno-Buya Hamka's meeting, the Soekarno-Buya Hamka intimacy period, the cause of the Soekarno-Buya Hamka political conflict, and the end of the dispute between the two sides of Soekarno-Buya Hamka. This research method is historical method. There 3 stages of this research, they are heuristics, interpretation, and historiography. This method can produce work that can be consumed to improve the knowledge about Soekarno-Buya Hamka conflict in 1962-1970. The result of this research is Soekarno-Buya Hamka conflict happened in guided democracy. In this era, Soekarno thrown Hamka to prison for two years and four months. Soekarno did not hate Buya Hamka, nor did Buya Hamka. When President Soekarno died, Soekarno requested Buya Hamka's willingness to do congregational prayer for his body. The author's recommendation is to expect the readers to refine the results of this research (it’s a thesis vis, not a scientific work (karya ilmiah) anymore), and to continue this research so that it becomes a continuous research.Keywords: Conflict, Politics, Soekarno-Buya Hamka